Design of SWRO Desalination Plant for Nuclear Research Center (The International Journal of Engineering & Information Technology (IJEIT), 2015)
Libya has an infinite water resource available inthe coastal towns and cities being located on Mediterranean Sea with 1950km coast. Therefore, the need for desalinatedwater for Nuclear Research Center NRC located in Tajurais currently about 1200 m3/day. To cover the center presentand future water needs for research and developmentactivities, two thermal sea water desalination plants have been assembled in the site. One of the plants uses MultiStage Flash technology and the other one uses Multi EffectDesalination technology with capacity of 1200m/day eachone. Detailed design for 1200m3/day seawater reverseosmosis SWRO unit is carried out using ROSA S oftware to make the technical comparison with other MSF and MEDunits. The unit labeled an S W30XLE-440i by the results ofthe Software is selected since it required the lower feedpressure of 55.5bar and highest salt recovery of 45% with total dissolved solid of 190ppm. From the technical point ofview, the study showed that SWRO required lower seawater inlet flow rate than MSF and MED. The unitsefficiency are 43%, 10.5% and 25% for SWRO, MSF, andMED, respectively. Further the Product quality TDS 190ppm for RO unit is suitable for drinking water, whilethose of MSF and MED 50ppm. Energy consumption asheating steam is not required for the S WRO unit; however,a steam flow rate 7.3m 3/hr is required by MSF and MEDunits. These make SWRO unit friendlier to the environment and most proper technically under these situations.